Thinking the body as a basis, provocation and burden of life. (Challenges of life., 2015)
The body is at the same time a place where we express duration and/or discontinuity in history, a witness of radical social changes, and a factor of stabilization and transformation of human life - and therefore an eminent challenge for every human being. This book will contribute in an interdisciplinary and cross-cultural way to a better understanding of the place, role, and connection of the body within social, political, and cultural shifts.